Effect of Storage Containers on Seed Quality of Barley (Hordeum vulgare L.) during Storage - SIDDU APPASAHEB KURUBAR; AXAY BHUKER; PUNEETHARJ MS; VS MOR; SS JAKHAR (Seed Research, 2026)
The study was conducted on seeds of three two-rowed varieties viz. BH 885, DWRB 92, DWRB 101and three six-rowed rowed barley varieties viz. BH 946, BH 393, BH 902 at CCS HAU, Hisar, Haryana (India)during 2020-21. The seeds of all barley varieties were stored in ordinary (Cloth bags) and moisture-proof (Polythenebags>700gauge thickness) containers under ambient conditions and observations were recorded on seed qualityparameters upto 9 months at three months. The results revealed that maximum test weight (48.71g), dry seedlingweight (234.00mg), and vigour index-II (20608) were recorded in DWRB 92. Variety BH 393 recorded maximumseedling length (27.83cm) and minimum test weight (26.64g), and germination (94.33%). Variety DWRB 101recorded maximum germination (97.67%) and vigour index-I (2488) while this variety recorded minimum seedlingdry weight (161.50mg) and vigour index-II (14946) after 9 months of storage. Variety BH 902 recorded maximumelectrical conductivity (196.64 μS/cm/seed) and BH 885 recorded minimum (148.24 μS/cm/seed).The highestvalue of field emergence (8.90) index was observed in BH 393, while the lowest (6.07) was in BH 946. Topseedlingestablishment(89.83%) was observed in BH 393, whileminimum (85.83%) was in BH 885.Polythene bag recordedmore test weight (39.08g), germination (94.61%), seedling length (28.70cm), seedling dry weight (193.72mg),vigour index-I (2599), vigour index-II (17523), field emergenceindex (8.13),seedling establishment(87.78%)andminimum electrical conductivity (160.79 μS/cm/seed) as compared to cloth bag which registered less test weight(38.82g), germination (94.61%), seedling length (25.16cm), seedling dry weight (185.67mg), vigour index-I (2165),vigour index-II (15911)field emergenceindex (7.00), seedling establishment (86.11%) and maximum electricalconductivity (179.45μS/cm/seed). It was concluded from the study thatBarley seed quality can be maintained inpolythene bags under ambient conditions for a longer period as compared to cloth bags when stored with optimummoisture content. Among six-rowed barley varieties, BH 393 performed better in all the quality parameters while inthe case of two-rowed barley varieties DWRB 101 performed best. These varieties can be used in further breedingprogrammes.